2021
DOI: 10.3390/nu13051414
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Practice and Food Stockpiling for Disaster

Abstract: In this study investigated the association between health practices and food stockpiling for disasters in predicted areas with a high risk of food shortage due to the Nankai Trough earthquake. A survey was conducted during 18–20 December 2019 using a self-administered web-based questionnaire. In total, 1200 individuals registered with an online survey company participated in the study. The association between health practices and food stockpiling status was analyzed (n = 998). 59.1% of participants had a poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a another Japanese study of 5540 adolescents aged 12 to 13 years, physically inactive was significantly associated with constipation [10]. In the third Japanese study, 9,234 subjects aged over 18 years, poor physical activity was significantly associated with constipation [11].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a another Japanese study of 5540 adolescents aged 12 to 13 years, physically inactive was significantly associated with constipation [10]. In the third Japanese study, 9,234 subjects aged over 18 years, poor physical activity was significantly associated with constipation [11].…”
Section: Discussionmentioning
confidence: 92%
“…In Icelandic, Swedish, Hong Kong, two Chinese and three Japanese studies showed the inverse association between constipation, functional constipation, and PA [4][5][6][7][8][9][10][11]. On the other hand, In US, British, and two Spanish studies were no association between PA and constipation was found [12][13][14][15].…”
Section: Introductionmentioning
confidence: 93%
“…Initially the variables were evaluated using univariable analysis, followed by a multivariable analysis (forced entry method) to adjust for some factors. The adjusted factors, among the participants’ characteristics, were factors associated with food stockpiling in a previous study [ 18 ]; including sex (male or female), age (20–34, 35–59 and ≥60 years), educational background (below undergraduate, or above college degree), and community activities (participating or not participating). In total, 1192 responses were recorded into the logistic regression model, after excluding responses related to sex and educational background as “others” (n = 3 and n = 8, respectively).…”
Section: Methodsmentioning
confidence: 99%